Revolutionizing Payment Systems: The Integration of TRAM and Trust in QRIS Adoption for Micro, Small, and Medium Enterprises in Indonesia - Nurqamarani, Adisthy Shabrina; Fadilla, Sarah; Juliana, Ari (Journal of Information Systems Engineering and Business Intelligence, 2024)
Background: In an era where digital finance is growing rapidly, the Quick Response Code Indonesian Standard (QRIS) revolutionizes the payment system through a single unifying code. This study brings novelty in integrating TRAM and Trust in the adoption of QRIS in micro, small, and medium enterprises (MSMEs) in Indonesia, for which studies are still limited. Objective: To observe determinants of QRIS adoption by integrating the Technology Readiness Acceptance Model (TRAM) and Trust in the emerging Indonesian market where QRIS is in a growing stage. Methods: This study collects data through the survey of 210 MSME owners and staff who are familiar with and/or have used QRIS through convenience sampling. In analyzing the data, this study uses the Structural Equation Model-Partial Least Square (PLS-SEM) to examine the relationship between variables that explain influencing factors of QRIS adoption. Results: The results show that 7 of 13 hypotheses were accepted; optimism and trust positively significantly affect perceived ease of use and perceived usefulness, while insecurity and innovation have no significant influence on perceived ease of use and perceived usefulness. Besides, this study shows unexpected positive results between discomfort, perceived ease of use, and perceived usefulness. Overall, the proposed TRAM and Trust model contributes 60.9 % in explaining QRIS adoption. Conclusion: This study emphasizes the importance of optimism, discomfort, trust, perceived ease of use, and perceived usefulness in influencing QRIS adoption in micro and small businesses in Indonesia. It guides QRIS providers, policymakers, financial institutions, and MSMEs in having effective QRIS adoption in business operations. Keywords: Micro Small and Medium Enterprises, QRIS, TRAM, Trust